Unlocking the Potential of Pseudomonas aeruginosa SWUC02: Cell-Free Supernatant and Extracts for Controlling Anthracnose Disease and Inducing Resistance in Yellow Chilli Seedling - Natthida Sudyoung; Papattananpak Thiratanabordeechot; Siritron Samosorn; Kulvadee Dolsophon; Onanong Pringsulaka; Supaart Sirikantaramas; Akira Oikawa; Siriruk Sarawaneeyaruk (Tropical Life Sciences Research, 2025)
Chilli anthracnose is a significant constraint in chilli production and quality in cultivated areas worldwide. Alternative methods are being explored to avoid the use of chemical fungicides, including plant elicitors produced by beneficial microorganisms to enhance plant defense responses. However, studies on the use of biotic elicitors to control chilli anthracnose are limited. In this study, we investigated the efficacy of cell-free supernatant derived from Pseudomonas aeruginosa SWUC02 (CF-SWUC02) and its extracts on the antimicrobial activity and systemic resistance in yellow chilli seedlings. The anthracnose pathogen, Colletotrichum truncatum CFPL01, was isolated and assessed for its pathogenicity in yellow chilli and other varieties, exhibiting varying levels of susceptibility to anthracnose. CF-SWUC02 exhibited potential antimicrobial activity against several phytopathogens. Furthermore, it affected the mycelial growth and conidial germination of virulent C. truncatum CFPL01. The dichloromethane extract exhibited the highest efficacy in suppressing the growth of C. truncatum CFPL01, while the ethyl acetate extract demonstrated a significant reduction in anthracnose severity on both leaves and seedlings. The ethyl acetate extract also increased phenylalanine ammonia-lyase activity in treated seedlings, demonstrating the induction of plant immunity. In summary, the elicitor compounds present in CF-SWUC02 have the potential to reduce anthracnose severity either directly through pathogen inhibition or indirectly via stimulation of the plant defense responses. These findings provide valuable insights for the development of sustainable and effective strategies for the control of chilli anthracnose.